Institutional theory in international business and management - Tihanyi, Laszlo, Ph. D.; Devinney, Timothy M. 1956-; Pedersen, Torben (Advances in international management ;, 2012)
Institutional theory has been used increasingly by international business and management researchers to explain the behavior and strategies of multinational enterprises. If early international business research was dominated by the application of transaction cost and neoclassical economics, reviews of recent publications and conference programs suggest that the past decade has been dominated by the application of institutional theory. The 2012 volume of the "Advances in International Management" series represents the collection of an eclectic mix of contemporary research by leading and emerging scholars working on institutional theory. The contributions present new theoretical frameworks of institutions and propose interesting ideas that will provide the foundation for doctoral dissertations and research projects.